Influence of TiO2 crystallinity on TiO2 nanotube confined CdS nanoparticles for photocatalytic hydrogen production. Issue 8 (2nd August 2020) - Peng, Quanming; Peng, Guiming; Wu, Liangpeng; Wang, Xiaoyang; Wang, Nan; Li, Xinjun
Abstract: Crystallinity is recognized as an important parameter that influences the photocatalytic performance, meanwhile the confinement effect of TiO2 nanotube is efficient to improve the activity. But how TiO2 crystallinity affects the property of TiO2 nanotube-based catalysts remains unclear. Here, CdS nanoparticles inside of various temperature treated TiO2 nanotube (CdS-in-TiO2 NT) was obtained. With the increase of calcination temperature from 300 to 500 °C, the crystallinity of TiO2 nanotube is increased resulting in the enhanced hydrogen evolution property of CdS-in-TiO2 NT. When the calcination temperature is higher than 500 °C, TiO2 nanotube is gradually collapsed, which leads to the decrease of photocatalytic performance of CdS-in-TiO2 NT. Further photoluminescence measurements confirm that CdS-in-TiO2 NT-500 has most quenched PL emission, which is in accordance with the H2 production efficiency. The highest hydrogen production rate of CdS-in-TiO2 NT-500 is ascribed to the efficient confinement effect, good crystallinity of TiO2 nanotube, and accelerated charge separation efficiency.